Tokens or Trailblazers: Identity Construction of Occupants of New Inclusion-Driven Roles - Pazzaglia, Federica; Sonpar, Karan; Kulkarni, Mukta; Maheshwari, Navya (Journal of Management, 2026)
New roles birthed by organizational inclusion initiatives present an interesting puzzle. On the one hand, they hold the promise to foster inclusion objectives more directly through their formalization in the organizational structure. On the other hand, they tend to be ambiguous as to what occupants are expected to do and how to reconcile this with existing organizational goals and processes. Therefore, they create a burden for their occupants to create a role identity that legitimizes who they are and what they do. To address this puzzle, we draw on a qualitative study of early occupants of the newly created role of lady officer within the Indian military. We find that their role identity construction involved negotiating an optimal balance between professional and inclusion-informed identities through discursive and embodied identity work. Role occupants’ identity work initially emphasized elements of their professional identity and subsequently infused elements of departure informed by their views of the role. In doing so, they sought to shape interpretations of the role and craft a sense of role legitimacy. Our key contribution lies in developing an emergent theory of identity construction by occupants of inclusion-focused roles, illustrating their efforts to craft a role identity and a sense of legitimacy for their role and themselves in it amid challenges posed by role ambiguity and by societal and organizational tensions.